Aktivitas insektisida ekstrak buah Piper aduncum L. (Piperaceae) dan Sapindus rarak DC. (Sapindaceae) serta campurannya terhadap larva Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) - Yan Yanuar Syahroni; Djoko Prijono (Perhimpunan Entomologi Indonesia, 2013)
Crocidolomia pavonana is an important pest of Brassicaceous vegetable crops. Botanical insecticides are potential alternatives for the control of C. pavonana pest. Insecticidal activity of Piper aduncum and Sapindus rarak fruit extracts as well as their mixtures was evaluated against C. pavonana larvae in the laboratory. Ethyl acetate P. aduncum (EtPa) extract as well as methanolic S. rarak (MeSr) and aqueous S. rarak (AqSr) extracts were tested separately and in mixtures against second-instar larvae C. pavonana by a leaf-residue feeding method. At the LC95 level - 72 hours after treatment (HAT), EtPa extract was about 14.5 and 12.8 times, respectively, more toxic to C. pavonana larvae than MeSr and AqSr extracts. At the LC95 level, EtPa + MeSr extract mixture (1 : 10 w/w) was about 1.64 times more toxic to the test larvae than EtPa + AqSr extract mixture (1 : 10 w/w). Based on combination index at 48, 72, and 96 HAT, EtPa + MeSr extract mixture at LC50 level as well as EtPa + AqSr extract mixture at LC50 and LC95 levels had additive joint action, whereas EtPa + MeSr extract mixture at LC95 was weakly synergistic. In addition to lethal effect, the treatment with all test materials delayed the development of C. pavonana larvae from second-instar to fourth instar. Thus, EtPa, MeSr, and AqSr extracts as well as the mixtures between EtPa and S. rarak extracts are potential alternatives for the control of C. pavonana pest.